Dampak Coronavirus Terhadap Revenue Growth Perusahaan Sub. Sektor Hotel, Restoran, dan Pariwisata - Jehezkiel Christanto; Lulu Setiawati (Publikasi Indonesia, 2021)
The research was conducted by wabah corona virus is happening in Indonesia and in some parts of the country. The impacts not only affect public health and security but have a major impact on the economy in all sectors, one of which is the tourism sector. This study aims to analyze the revenue growth of companies in the hotel, restaurant and tourism sub-sector before and after the corona virus. The method used in this research is quantitative by using the analysis technique paired sample t-test. Based on the results in this study, it shows that there is a difference in revenue growth in the sub-sector of hotels, restaurants and tourism before and after corona virus negatively. This decline is indicated by a decrease in the number of tourists due to the corona virus